The Chinese Nightingale, and Other Poems - Lindsay, Vachel, 1879-1931 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Chinese Nightingale and Other Poems" by Vachel Lindsay is a collection of poems written during the early 20th century. This work captures themes of beauty, nostalgia, and cultural exploration through a lens both personal and imaginative, reflecting on the richness of Chinese folklore alongside contemporary societal issues. The opening of the collection introduces "The Chinese Nightingale," a poem that begins with a dialogue between two characters, one named Chang, who draws upon his memories of a vibrant past filled with love and beauty, contrasted against the mundane life of a laundryman in San Francisco. The poem evokes a sense of longing for a lost world, filled with mythical imagery and a nightingale that symbolizes beauty and love, as it reminisces about the vibrant culture of old China. Through this rich tapestry of words, Lindsay weaves a narrative that speaks to the universality of love and the impact of time on human experience, providing a glimpse into the emotional depth present in the rest of the collection. (This is an automatically generated summary.)
Release date is 1996-07-01
Produced by A. Light
Keywords: World War, 1914-1918 -- Poetry; American poetry; Fairy tales -- Poetry